Anaerobic Co-digestion of Catering and Agro-Industrial Waste: A Step Forward Toward Waste Biorefinery - Anjum, Muzammil; Qadeer, Samia; Khalid, Azeem (Frontiers in Energy Research, 2018)
In the present study, a biorefinery system is proposed using catering and agro industrial waste for biogas and low phytotoxic digestate. Anaerobic co-digestion of catering waste with partially pre-treated (microwave 800 J/g/min + steam 121 °C 40 min) maize crop residues was conducted under different composition (20–50%) of feedstock. The results showed that the biogas production was increased by 2.03 times in co-digestion experiment (40% partially pre-treated maize crop residue + 60% catering waste: TCM3) as compared to catering waste alone (control). The increment in accumulative methane 116.7 m3 t−1 was recorded in TCM3 which is due to improvement in biodegradation under co-digestion process. The post digestion byproduct (residual digestate) was evaluated for its phytotoxicity which is supplied with aerobic post treatment. The post treatment has improved the digestate quality by decreasing VS/TS ratio from 259 to 173 g/L and slightly increase the pH from 7.29 to 8.32. Seed germination assay showed that the germination percentage (G%), germination index (GI) and vigor index (VI) were relatively higher with post treated digesate as compared to un-treated digestate. In the germination test using wheat seeds, the post treated digestate (5% sol. extract) achieved higher values of GI and VI (46 and 609) whereas in un-treated, values for these indices were 14 and 62, respectively. Overall the findings of the present study identify the significance co-digestion based waste biorefinery, in order to development of value added bio-products such as biogas and biofertilizers.